2011
DOI: 10.1371/journal.ppat.1002045
|View full text |Cite
|
Sign up to set email alerts
|

Dual Function of the NK Cell Receptor 2B4 (CD244) in the Regulation of HCV-Specific CD8+ T Cells

Abstract: The outcome of viral infections is dependent on the function of CD8+ T cells which are tightly regulated by costimulatory molecules. The NK cell receptor 2B4 (CD244) is a transmembrane protein belonging to the Ig superfamily which can also be expressed by CD8+ T cells. The aim of this study was to analyze the role of 2B4 as an additional costimulatory receptor regulating CD8+ T cell function and in particular to investigate its implication for exhaustion of hepatitis C virus (HCV)-specific CD8+ T cells during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
99
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 103 publications
(110 citation statements)
references
References 42 publications
6
99
2
1
Order By: Relevance
“…Molecular mechanisms for CD244 modulation of T-cell responses in infections remain unknown, although CD244 appears to regulate NK cell function that correlates with HBV or HCV persistence in humans (40,41). In this study, we find that human TB can upregulate CD244 and CD244 signaling-related molecules in CD8 + T cells.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Molecular mechanisms for CD244 modulation of T-cell responses in infections remain unknown, although CD244 appears to regulate NK cell function that correlates with HBV or HCV persistence in humans (40,41). In this study, we find that human TB can upregulate CD244 and CD244 signaling-related molecules in CD8 + T cells.…”
Section: Discussionmentioning
confidence: 58%
“…It has recently been shown that CD244 is expressed on virus-specific CD8 + T cells (9,(39)(40)(41) and that CD244 signaling correlates with viral persistence of hepatitis B virus (HBV) and HCV in humans (9,39,40). However, little is known about the molecular mechanism and consequence for CD244 regulation of T-cell effector functions during active TB infection.…”
Section: T Uberculosis (Tb) Caused By Mycobacterium Tuberculosis (Mtb)mentioning
confidence: 99%
“…This observation is well in line with our recent findings in patients with chronic hepatitis C where we also found that targeting two different costimulatory or coinhibitory receptors had no synergistic but rather counteractive effects. 30 Similarly, nonredundant roles for the CTLA-4 and PD-1 pathways have been described in driving T-cell exhaustion in chronic hepatitis B. 47 Overall, these data indicate an individual ''private'' costimulatory receptor usage of T-cells during viral infections.…”
Section: Discussionmentioning
confidence: 87%
“…Immune responses against HEV were studied in a total of 38 subjects including 19 healthy immunocompetent individuals and 19 immunocompromised organ recipients. The immunocompetent group included anti-HEVpositive (''exposed'') subjects (n ¼ 9; median age 32; range 26-66) and anti-HEV-negative (''no exposure'') individuals (n ¼ 10; median age 30; range [25][26][27][28][29][30][31][32][33][34][35][36][37]. The immunocompromised group included transplanted patients who developed chronic hepatitis E (n ¼ 7; median age 49; range 34-66) and transplanted patients who resolved HEV infection (n ¼ 12; median age 53; range 27-69).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation